2015
DOI: 10.1149/2.0191509jss
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric Multicycle Rapid Thermal Annealing: Enhanced Activation of Implanted Dopants in GaN

Abstract: Selectively activated p-type regions are necessary for many electronic devices that require planar processing. The standard process of implanting p-type dopants, such as Mg, in GaN is notoriously more difficult than in other material systems, as the extremely high temperatures required to activate the implanted Mg also damage the GaN surface. In this research, a novel annealing technique is introduced for this purpose -symmetric multicycle rapid thermal annealing (SMRTA). It is shown that SMRTA is superior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…The total time at high temperatures can be extended to hours under these conditions, although it is recognized that there may be significant Mg diffusion during such long time anneals. As noted earlier, earlier studies based on Mg‐implanted GaN/sapphire structures possess a high intrinsic defect density (>10 8 cm −2 ) . Using high‐quality GaN substrates can promote homoepitaxial GaN film growth with a much lower intrinsic defect concentration (<10 6 cm −2 ) and is anticipated to further improve device performance as well as the ability to separate implant‐induced defects from those in the preexisting heteroepitaxial structure.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The total time at high temperatures can be extended to hours under these conditions, although it is recognized that there may be significant Mg diffusion during such long time anneals. As noted earlier, earlier studies based on Mg‐implanted GaN/sapphire structures possess a high intrinsic defect density (>10 8 cm −2 ) . Using high‐quality GaN substrates can promote homoepitaxial GaN film growth with a much lower intrinsic defect concentration (<10 6 cm −2 ) and is anticipated to further improve device performance as well as the ability to separate implant‐induced defects from those in the preexisting heteroepitaxial structure.…”
Section: Introductionmentioning
confidence: 73%
“…In any case, the Mg dopant activation requires annealing at a much higher temperature (≥1300 °C), but the critical issue is that the decomposition of GaN is significant at 840 °C at one atmosphere, which is well below the dopant activation annealing temperature. Annealing techniques have been developed to overcome this issue, including microwave‐based annealing and multicycle rapid thermal annealing (MRTA) . Both techniques utilize a fast heating source that can reach high temperatures while keeping the total anneal time short.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the extremely high temperatures required to activate the implanted Mg during the annealing process also damage the GaN surface [61,62]. Greenlee, J.D., et al [63] reported that the second annealing process followed by multicycle rapid thermal annealing (MRTA) process can compensate for the defects of the GaN surface and improve the crystalline quality of implanted p-GaN.…”
Section: Field Ringsmentioning
confidence: 99%
“…Mg) requires an annealing temperature over 1300°C [39], which causes the decomposition of GaN at atmospheric pressure. The decomposition brings about a loss of nitrogen, surface damage and the creation of nitrogen vacancies [33,40]. In order to prevent the loss of nitrogen loss at the GaN surface, it is desirable to deposit a high-quality capping layer before the annealing step, followed by a reliable removal process after annealing [41].…”
Section: Activation Of Implanted P-type Ganmentioning
confidence: 99%
“…The MRTA process enabled the activation of implanted Mg with activation efficiency of over 8% and the demonstration of p-type conductivity [42]. Although the implantation-induced lattice damage can be restored by the proposed MRTA process, additional structural changes in the GaN sample were created because of the process with rapid heating and cooling cycles [33]. To overcome this issue, a modified MRTA process has been developed by introducing an conventional annealing step after the multi rapid heating and cooling cycles as shown in Fig.…”
Section: Activation Of Implanted P-type Ganmentioning
confidence: 99%